2013
DOI: 10.1039/c2bm00032f
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of nano-topography on the surface of a bone-implant

Abstract: Bone-implant material development is proceeding at a high pace, and has shifted from straightforward biomaterial testing to more advanced cell-targeted approaches for surface modification and design.It has been long known that cells can recognize and respond to topographical features by changing their morphology and behavior. The progress in surface analytical devices, as well as in techniques for production of topographical features on the nanometer scale allow for the characterization of natural tissues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 162 publications
1
53
0
Order By: Relevance
“…The human body is an exceedingly complex, precise and ordered hierarchical organization, in which all components work together in harmony across a wide range of dimensions [18]. From such a biomimetic viewpoint, a bio-inspired structure should be able to incorporate both the ordered microstructure and ordered nanostructure mimicking the architecture of the natural extracellular matrix in bone tissues to induce all of the osteoblasts functionality [19][20][21]. It has been demonstrated that the synergistic effects of micro-and nano-textural surface are also favourable to all life processes in cell adhesion, spreading, proliferation and osseointegration [11,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The human body is an exceedingly complex, precise and ordered hierarchical organization, in which all components work together in harmony across a wide range of dimensions [18]. From such a biomimetic viewpoint, a bio-inspired structure should be able to incorporate both the ordered microstructure and ordered nanostructure mimicking the architecture of the natural extracellular matrix in bone tissues to induce all of the osteoblasts functionality [19][20][21]. It has been demonstrated that the synergistic effects of micro-and nano-textural surface are also favourable to all life processes in cell adhesion, spreading, proliferation and osseointegration [11,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Further guidelines for cell behavior initiated by nanopatterned polymer surfaces can be found elsewhere. [54,122] …”
Section: Protein Adsorption On Nanostructured Amorphous Polymer Surfacesmentioning
confidence: 99%
“…Remarkably, isotropic and anisotropic macro-, micro-and nanometer-sized features seem not only to be effective on the organ level, but also can stimulate various types of cell-behavior. Multiple in vitro studies have shown that attachment, migration, proliferation and differentiation can be manipulated by utilizing different topographies on culturing surfaces (reviewed in [5]). The fact that cells have evolved to interact with the likewise hierarchically organized extracellular matrix (ECM) allows speculations about the ability of a modern implant surface to interact with cellular functions in a more natural way, while stimulating desirable behavior.…”
Section: Introductionmentioning
confidence: 99%